MAKING SILL TABLE WITH THE MATERIAL OF WOOD WASTE AND RESIN - Naim, Sultono bin; Irwanto, Asep Ahmad Ruri (Universitas Pendidikan Indonesia, 2020)
ABSTRACT â€“ The activity of workshop practicum construction materials-based, Construction Engineering of Civil Engineering Education Departmentâ€™s Workshop, produces wastes such as woods pieces, sawdust, galvanized pipe pieces/PVC that are still not able to utilized maximally. Every semester, yield of the practicum activity becomes waste. The research making table from wood waste and resin is one of solution and innovation to utilize the waste to become having more economic values. In the previous study, with physical and mechanical test, it could be found that the tighter the assembly of wood waste, the stronger its capability to hold its tensile force.This research used qualitative method. From the supervising of the steps of making sill table from the material of wood waste and resin, there is one type of sill table which was implemented in this research, it is split the wood waste into elongated. This research was done by three times trials with different kinds formula of resin and catalyst.The result of this research is the steps and formula of the volume comparison of resin and catalyst to make sill table from waste and resin that could be a learning guidance for woods construction practice subject and interior finishing practice subject in Construction Engineering Education Study Program and giving solution as a form of responsibility for waste handling.Â Keywords: Wood waste, Table, Resin.